Aplicação do princípio da fungibilidade recursal aos embargos de declaração recebidos como agravo - Mesalira, Daisy (2014)
The present work aims to analyze the principle of fungibility, the appellate level, conceptualizing this guideline if we discuss and contextualize up the other principles that are added to the theme. Although, to apply the principle when it handles requests for clarification against monocratic decision of the rapporteur, this will be received as an internal grievance or regimental grievance, since it is understood that the embargo would not be appropriate to attack this decision. We focus where the part may suffer prejudice through the application of appellate fungibility, inasmuch as, it is cited problematic of limited depth of the theme addressed in this appeal footstool, opposite depth discussion that can be seen in the Appeal, which includes a wider reasoned